2016
DOI: 10.1128/jvi.03069-15
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in a Highly Conserved Motif of nsp1β Protein Attenuate the Innate Immune Suppression Function of Porcine Reproductive and Respiratory Syndrome Virus

Abstract: Porcine reproductive and respiratory syndrome virus (PRRSV) nonstructural protein 1␤ (nsp1␤) is a multifunctional viral protein, which is involved in suppressing the host innate immune response and activating a unique ؊2/؊1 programmed ribosomal frameshifting (PRF) signal for the expression of frameshifting products. In this study, site-directed mutagenesis analysis showed that the R128A or R129A mutation introduced into a highly conserved motif ( 123 GKYLQRRLQ 131 ) reduced the ability of nsp1␤ to suppress int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 65 publications
3
27
0
Order By: Relevance
“…This finding was consistent with a previous report that once nsp1␤ was cleaved from nsp2 by autoproteolytic activity, PLP1␤ in nsp1␤ became inactive due to self-blocking by the conformational change of its own C-terminal extension (CTE) (76). A highly conserved domain had previously been identified within the PLP1␤ region (17,19), and L126 is one of the most critical residues that support nsp1␤ function (Fig. 4B) (19).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This finding was consistent with a previous report that once nsp1␤ was cleaved from nsp2 by autoproteolytic activity, PLP1␤ in nsp1␤ became inactive due to self-blocking by the conformational change of its own C-terminal extension (CTE) (76). A highly conserved domain had previously been identified within the PLP1␤ region (17,19), and L126 is one of the most critical residues that support nsp1␤ function (Fig. 4B) (19).…”
Section: Discussionsupporting
confidence: 92%
“…The SAP motif in nsp1␤ overlaps the highly conserved sequence 123 -GKYLQRRLQ-131 in PRRSV (18) and is also identified in lactate dehydrogenase-elevating virus (LDV) and simian hemorrhagic fever virus (SHFV), but not in equine arteritis virus (EAV), in the family Arteriviridae. Mutations in the nsp1␤ SAP motif have conferred clinical attenuation of PRRSV in pigs (17,18,23). In our study, the SAP motif has been shown to be critical for nsp1␤-mediated host mRNA nuclear retention (19).…”
mentioning
confidence: 53%
See 1 more Smart Citation
“…The cell culture supernatant was harvested at 0, 24, 48, 72, and 96 hpi. The virus titers were measured by a microtitration assay using Marc-145 cells in 96-well plates and calculated as TCID 50 per milliliter according to the method of Reed and Muench (33). The sera from infected piglets were also probed by the same method.…”
Section: Cells Antibodies and Virusesmentioning
confidence: 99%
“…PRRSV whose PLP1b active sites are mutated is non-viable, indicating that PLP1b is essential for virus replication (Kroese et al, 2008). The PLP1b activity in nsp1b also regulates the generation of nsp2TF via À1/2 ribosomal-frameshifting (Fang et al, 2012;Li et al, 2016). A nuclease motif has been identified at K18-E32 in the N-terminal region of nsp1b (Xue et al, 2010), but this motif is irrelevant to IFN suppression (Han et al, 2014).…”
Section: Nsp1bmentioning
confidence: 99%